Intellectual Security and Artificial Intelligence: Managing the Balance Between Positivity and Negativity - Raheef, Oparinde Olayiwola; Olayiwola, Shina Olawale; Oni A., Lawrence (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Artificial Intelligence (AI) is rapidly reshaping how individuals, institutions, and nations interact with knowledge and information. Beyond its promise to revolutionize decision-making and productivity, artificial intelligence (AI) presents difficult problems for intellectual security, which protects knowledge integrity, autonomous thought, and freedom from manipulation. The problem is made much more urgent in Nigeria, where there is a disparity in digital literacy and AI policy frameworks are still developing. Therefore, this study explored strategies for balanced AI use, highlighting the importance of strong ethical frameworks, legal limitations, and public education campaigns. The study adopted a convergent parallel mixed-method design, combining quantitative surveys with qualitative interviews for triangulation. Surveys and interviews were conducted with 300 respondents and 15 key informants across Osun, Lagos, and Abuja with the help of three research assistants. A structured questionnaire and semi-structured interview guide were used to collect information from the respondents. The quantitative data were analyzed using descriptive statistics, and the qualitative data were analyzed thematically using NVivo 12 software. Results showed strong perceptions of AI’s benefits in information access and productivity but also concerns over misinformation and data manipulation. It was concluded that AI is a reflection of its design and is neither good nor harmful. This research is significant because it provides a balanced inquiry into AI’s benefits and risks, offering evidence-based insights to guide policymakers, educators, and society in navigating an AI-driven future. It alsoenriches debates in AI ethics and digital sociology by framing AI as both a cognitive enabler and a potential manipulator.